Animación virtual tridimensional para la difusión cultural de las formas arquitectónicas de la hacienda Tilipulo como patrimonio de la ciudad de Latacunga - Álvarez Sangoquiza, Ángel Mesías (2013)
The starting point for the development of the research was the Graphic Design as a means of cultural dissemination, along with elements of Multimedia Design. Components present in any other graphic field, such as color, shape, typography, among others. In the thesis the 3D design, played an important role as this depended on the success of multimedia production. Furthermore, it`s highlighted the development of the Script Multimedia, in which is detailed step by step the tour through Tilipulo building. The study shows that much of the people unknown the value the architectural forms that the “Hacienda Tilipulo”, has being necessary to capture a new image of the same one, and a better way to do it`s by using new technologies such as the third dimension starting from architectural modeling to create the animation. This will help to strengthen the culture of the community through the use of new diffusion strategies.